Synthesis of GDC electrolyte material for IT-SOFCs using glucose & fructose and its characterization - Medisetti, S.; Ahn, J.; Patil, S.; Goel, A.; Bangaru, Y.; Sabhahit, G.V.; Babu, G.U.B.; Lee, J.-H.; Dasari, H.P. (Elsevier B.V., 2017)
Nano-powder of gadolinium-doped-ceria (GDC, Ce0.9Gd0.1O2) has been synthesized using a novel sol？gel method with glucose and fructose as organic additives. The main objective of the present study is to find the suitability of this synthesis method in synthesizing ceria-based SOFC electrolyte materials and evaluate its performance. The average crystallite/particle size obtained from XRD, TEM, BET surface area was found to be 4？12 nm. The phase was found to be cubic fluorite from XRD and further the structure and the nature of oxygen vacancies was confirmed using Raman spectroscopy. Dilatometer studies illustrated two shrinkage maxima (450 °C and 1450 °C). The ionic conductivity measurements were done using DC four-probe method on the GDC electrolyte sintered at 1500 °C. The sintered sample showed an ionic conductivity of 1.13E？02 Scm？1 at a temperature of 700 °C in the air, and the activation energy is 1.02 eV. The present study reveals that this synthesis method can be adaptable for synthesizing SOFC electrolyte materials. ？ 2017 Elsevier B.V.